A magyar zsidóság jogfosztása a büntetőjogi gyakorlatban - Lehotay, Veronika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
In the course of the research and in the study, I seek to answer the following questions: how have the categories of crime changed as a result of the restrictive laws and the war? How were convictions handed down? What was the role of the Royal Tribunal of Miskolc in the initiation and enforcement of proceedings under the Jewish Laws of 1938-1944 and in the implementation of discriminatory jurisprudence? I have narrowed down the time frame, the explanation for which is that by 1944, a significant part of the twenty-one Jewish laws and their related decrees were already in force and had become part of the jurisprudence of the courts. In addition to the Jewish Laws, other 'typical' crimes of the period, such as those committed in the context of national defence.